(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Eranda Bhrishta Haritaki (EBH) is a popularly used Ayurvedic medicine indicated in the management of Vatavyadhi, Amavata (rheumatoid arthritis), Grudhrasi (sciatica) etc where Vatanulomana plays a prime role. Despite of the wide range of use and popularity among the Ayurveda practitioners, there are very few scientific documents available for the reference of parameters of standardization, especially in the method of preparation of this formulation. In this study the standardization processes included identifying crude drug characteristics, pharmacognosy study and pharmaceutical analysis of the finished product along with the standardization of method of preparation. The results indicated consistency across batches, with values falling within standard limits, thereby confirming the formulation’s reliability. The study successfully established a standardized protocol for EBH preparation, highlighting its therapeutic potential and reinforcing the importance of quality control in herbal medicine. This comprehensive approach paves the way for further clinical application and research in Ayurveda formulations.